An Oncoplastic Breast Augmentation Technique for Immediate Partial Breast Reconstruction following Breast Conservation. Issue 2 (February 2017) - Barnea, Yoav; Friedman, Or; Arad, Ehud; Barsuk, Daphna; Menes, Tehillah; Zaretski, Arik; Leshem, David; Gur, Eyal; Inbal, Amir
Abstract : Background: Patients with a small breast volume and a relative large lumpectomy volume are at risk of developing severe breast deformity and asymmetry following breast conservation, presenting a unique surgical challenge. Methods: A series of patients undergoing immediate reconstruction by means of an oncoplastic breast augmentation technique following breast conservation are described. The technique includes local tissue rearrangement and bilateral subpectoral breast augmentation with implants of different sizes and shapes, immediately after lumpectomy for a malignant tumor. Results: Twenty-one consecutive patients underwent the oncoplastic breast augmentation technique (mean follow-up, 23 months; range, 12 to 48 months). Three patients (14.3 percent) had tumor-positive surgical margins. Postoperative complications included grade III/IV capsular contracture in five patients (23.8 percent) and breast infection in two patients (10 percent). All patients received postoperative radiation therapy. The cosmetic outcome was evaluated at least 6 months after radiation therapy, and it was favorable according to the reported high patient satisfaction (81 percent) and independent observers' evaluation scores (76 percent). Conclusions: The oncoplastic breast augmentation technique described in this article is an acceptable option in small-breasted patients with a relatively large lumpectomy volume who elect to undergo breast conservation. This technique allows conservation of the affected breast and minimizes potential breast deformation and asymmetry following radiation therapy. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.